2014
DOI: 10.1007/s10549-014-2893-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of breast cancer in thyroid diseases: results of a cross-sectional study of 3,921 patients

Abstract: Results from national cancer registries reveal an association of thyroid cancers with extra-thyroidal malignancies. In this study, we evaluated the prevalence of breast cancer (BC) in women affected by both benign and malignant thyroid diseases (TD) in comparison to the general population. To this end, 3,921 female patients from central and southern regions of Italy were evaluated. Age-matched analysis of the prevalence of BC was carried out after dividing the patients into three diagnostic categories: (1) 1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 38 publications
3
36
1
Order By: Relevance
“…We found that BC patients had higher levels of TPOAb and TgAb than controls. However, our findings were in disagreement with those of Prinzi et al (2014), who showed that the presence of thyroid auto-antibodies is protective against BC. That study differed from the current study in that they used qualitative data to determine thyroid disease, and they showed functional sensitivities for TgAb (positivity﹥60 U/ml) and TPOAb (positivity﹥60 U/ml).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that BC patients had higher levels of TPOAb and TgAb than controls. However, our findings were in disagreement with those of Prinzi et al (2014), who showed that the presence of thyroid auto-antibodies is protective against BC. That study differed from the current study in that they used qualitative data to determine thyroid disease, and they showed functional sensitivities for TgAb (positivity﹥60 U/ml) and TPOAb (positivity﹥60 U/ml).…”
Section: Discussioncontrasting
confidence: 99%
“…However, we were unable to identify any association between nuclear grade, ER, PgR and HER2̸neu status, lymph node involvement and TPOab positivity. In March, 2014 a study conducted in Italy demonstrated that breast cancer prevalence is higher among patients with thyroid diseases; however, the subgroup analysis demonstrated that TPOab and/or antithyroglobulin antibody positivity appear to be protective against breast cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…This issue needs clarification with further research both pathophysiologically and clinically. Most of these studies have commonly emphasized the necessity of screening for breast cancer in patients with thyroid disorders [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%